An analysis of the drug error problem in the Thai Anesthesia Incidents Study (THAI Study) - Hintong T. (2014)
Objectives: To analyze the problem of drug error related to anesthesia in Thailand including nature, contributing factors and preventive strategies. Material and Method: We prospectively recorded anesthesia-related drug error incidents for 18 months in 20 studied hospitals in Thailand. Types of errors and their outcomes were recorded. All data were analyzed to identify contributing factors and preventive strategies. Results: Forty-one drug error incidents were reported in 40 out of 202,699 anesthetized cases or 1: 4,943 in this study. The most common type of error was wrong drug (20 incidents; 48.8%). No relationship between anesthetic techniques and the incidents except for a combined general and epidural technique. The errors were most commonly occurred during induction of anesthesia(26 out of 41; 63.4%) and muscle relaxants were most commonly involved(13 out of 41; 31.7%). The majority of incidents (26 out of 41; 63.4%) caused no adverse effect. However 14 incidents (34.1%) caused transient mild to severe physiological effects, of which 13 had complete recovery but one died. Haste and lack of recheck were two common contributing factors which were minimized by high awareness and double check prior to drug administration. Main strategies suggested to prevent the incidents included specific guideline development whereas the incidents did not effectively decrease by increasing of manpower. Conclusion: The incidence of drug error in our study was 1: 4,943. It can cause morbidity and mortality during anesthesia. Practitioners should be aware of these potential incidents and strictly follow the guideline for drug administration.